The influence of molasses concentration on the physical and mechanical properties of evaporation boat waste-based crucibles - Rusiyanto, Rusiyanto; Widodo, Rahmat Doni; Prasetyo, Ares Yudi; Fitriyana, Deni Fajar; Bahatmaka, Aldias; Sudiyono, Sudiyono; Setiadi, Rizki; Rengga, Wara Dyah Pita; Ismail, Rifky; Bayuseno, Athanasius Priharyoto; Priyatmojo, Anjar; Ramdhani, Wahyu; et al. (Penerbit UTHM, 2024)
Crucibles are critical equipment utilized across numerous industries, and they are notably costly. In this study, the influence of molasses concentrations on the properties of crucibles fabricated from evaporation boat waste products is explored. The evaporation boat waste was powdered and filtered using a 100 mesh sieve. The molasses concentrations added during the mixing procedure were as follows: 0%, 5%, 10%, 15%, and 20% by weight. After 120 minutes, the mixture was compacted using 25 MPa pressure. The green body formed was dried at 100°C for 300 minutes and fired at 1150°C for 240 minutes. The obtained specimens were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM), density testing, hardness testing, and flexural testing. The results of this study demonstrate that the addition of molasses has significant effects on the properties of the crucibles. Specimens using molasses with a concentration of 5 wt% produce better physical and mechanical properties than other specimens. The density, hardness, flexural strength, and weight percentages of Boron nitride (BN) and Titanium diboride (TiB2) phases in the specimen with 5 wt% molasses were 2.36 g/cm3, 64 HRA, 31.5 MPa, 68.9%, and 31.1%, respectively. The use of evaporation vessel waste and molasses in the production of crucibles in this study is in line with Sustainable Development Goals (SDGs) 3, 7, 14, and 15, which relate to improving excellent health and well-being, ensuring access to affordable energy, and conserving marine and terrestrial ecosystems.